A variant in MRPS14 (uS14m) causes perinatal hypertrophic cardiomyopathy with neonatal lactic acidosis, growth retardation, dysmorphic features and neurological involvement. (24th October 2018) - Jackson, Christopher B; Huemer, Martina; Bolognini, Ramona; Martin, Franck; Szinnai, Gabor; Donner, Birgit C; Richter, Uwe; Battersby, Brendan J; Nuoffer, Jean-Marc; Suomalainen, Anu; Schaller, André
Abstract: Dysfunction of mitochondrial translation is an increasingly important molecular cause of human disease, but structural defects of mitochondrial ribosomal subunits are rare. We used next-generation sequencing to identify a homozygous variant in the mitochondrial small ribosomal protein 14 ( MRPS14, uS14m ) in a patient manifesting with perinatal hypertrophic cardiomyopathy, growth retardation, muscle hypotonia, elevated lactate, dysmorphy and mental retardation. In skeletal muscle and fibroblasts from the patient, there was biochemical deficiency in complex IV of the respiratory chain. In fibroblasts, mitochondrial translation was impaired, and ectopic expression of a wild-type MRPS14 cDNA functionally complemented this defect. Surprisingly, the mutant uS14m was stable and did not affect assembly of the small ribosomal subunit. Instead, structural modeling of the uS14m mutation predicted a disruption to the ribosomal mRNA channel.Collectively, our data demonstrate pathogenic mutations in MRPS14 can manifest as a perinatal-onset mitochondrial hypertrophic cardiomyopathy with a novel molecular pathogenic mechanism that impairs the function of mitochondrial ribosomes during translation elongation or mitochondrial mRNA recruitment rather than assembly.